Five funny frights - Stamper, J. B. (New York Schoolstic, 1993)
High-interest storiest make reading fun! Stories have been tested for vocabulary and sentence lenght to help you make the right choice! A letter from an education specialist gives you valuable advice on how to read to your child and how to listen to your child read to you!
Keywords: Literature